Sintesis dan Karakterisasi Hidrogel Berbasis Selulosa dari Kulit Durian untuk Penjernihan Air Gambut - Raudhatul Fadhilah; Doddy Irawan; Tuti Kurniati (Jurnal Penelitian Pendidikan IPA, 2025)
Peat water in Indonesia, abundant in swamp regions, is acidic and rich in humic substances and Fe²⁺ ions, making it unsuitable for direct use. This study explores a sustainable approach to treating peat water using hydrogel synthesized from durian rind (Durio zibethinus), an agricultural waste rich in cellulose. Cellulose was extracted via alkali and bleaching treatment, then crosslinked with chitosan in a NaOH/urea solvent system to form a biodegradable, porous hydrogel. The hydrogel exhibited a swelling ratio of 857% and a gel content of 98.23%, indicating high hydrophilicity and network integrity. Adsorption experiments demonstrated removal efficiencies of 98.96% for methylene blue and 25% for Fe²⁺. The high dye removal at low concentrations suggests strong interaction between hydrogel functional groups (–OH, –NH₂) and organic molecules, while Fe²⁺ removal was attributed to electrostatic interaction and potential chelation. Adsorption followed pseudo-second-order kinetics, indicating chemisorption as the rate-limiting step. These results suggest that durian rind hydrogel is a promising low-cost material for organic and inorganic pollutant removal in acidic water systems. This study highlights the potential of agro-waste valorization in developing eco-friendly materials for water purification.